Commercialisation of non-timber forest products: review and analysis of research - Neumann, R.P.; Hirsch, E. (Center for International Forestry Research, 2000)
This study is one in a series of activities undertaken by CIFOR to reach a better understanding of the impact of commercialisation on forest resources and what factors influence the market demand for forest products. For example, two international workshops were organized by CIFOR in 1995 and another the following year to analyse key research issues in the field of NTFP development. These workshops recognised that the process of NTFP commercialisation interacts with people's welfare, forest management, tenure and control of resources, and forest structure and function (through ecological processes). Earlier review and analysis had generated a number of hypotheses, theories and conclusions related to the effects of commercialisation. Forest and resource tenure are likely to both affect the way a resource is managed and utilised, and be affected by changes in value due to commercialisation. Many authors have suggested that NTFP harvesting will be less damaging to biodiversity and other environmental values than management for timber. Others suggest that market pressures are likely to lead to the decline and eventual disappearance of valuable products and to severe impacts on the ecosystem. While there is a growing understanding (and acceptance) of the economic importance of forest products, especially for the poor, the potential impact of NTFP commercialisation needs to be better understood. A recommendation from the workshops was to undertake a thorough overview of the available literature to synthesise the key lessons about these areas of interaction. Such a review would critically examine the available information and analyses and identify key research areas needing further attention.